The Effectiveness of ATCS Use Policy in Improving Traffic Smoothness and Safety in Banjarbaru City - Reza Pahlevi; Budi Kristanto (Syntax Corporation Indonesia, 2025)
Researchers are interested in conducting research on the effectiveness of ATCS use policies in improving the smoothess and safety pf traffic in Banjarbaru City, because ATCS is a policy implemented by the Banjarbaru City government to reduce the level of congestion and also a form of public service in the traffic sector. This research was conducted with the aim of evaluating the effectiveness of ATCS use polocies in overcoming traffic problems in Banjarbaru City. The research uses qualitative research methods using interviews, observation and documentation to collect problem data based on facts. The research results show that the implementation of ATCS in Banjarbaru City has shown positive results in reducing congestion. With the ability to manage traffic dynamically, this system can adjust the timing of green and red lights based on the volume of passing vehicles. This is very important, especially during rush hour, where traffic tends to by heavy.